The Effect of Guessing Game on Students' Vocabulary Knowledge - Raudlatul Hasanah; Ismalianing Eviyuliwati; Maya Defianty (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of the study was to know and describe the effect of the guessing game technique on students’ vocabulary knowledge at the seventh grade of a state Islamic Junior High School (MTsN). This study applied a quantitative method and a quasi-experimental design. The samples of the study were chosen using the purposive sampling technique with a total number of 63 students. There were two classes consist of the Experimental class and the controlled class. The experimental class was taught by using the guessing game technique while the controlled class was taught by listening to the teacher’s explanation on the textbook’s material and doing assignments. The data were collected through pre-tests and post-tests and analyzed using a t-test. The result of the pre-test showed that the mean score of the experimental class was 57.9 and the controlled class was 68.54. However, after being given guessing game treatment, the experimental class mean score increased up to 78.4 while the controlled class mean score was 70.93. It means that Ha was accepted. In addition, the effect size was 1.0 (moderate effect). Therefore, it can be concluded that there was a significant effect of using the guessing game technique on students’ vocabulary knowledge at the Seventh Grade of a state Islamic Junior High School (MTsN) .Keywords: Vocabulary, Knowledge student of Islamic School, Guessing game